2x^2 - 12x + 11
2(x^2 - 6x) + 11
2(x^2 - 6x + 9) + 11 - 2*9
2(x-3)^2 - 7
Rewrite by completing the square.
2x^2 - 12x + 11
2 answers
2 x ^ 2 - 12 x + 11 =
2 ( x ^ 2 - 6 x ) + 11 =
______________________________________
Take one half of the coefficient of x and square it.
In this case : [ ( 1 / 2 ) * 6 ] ^ 2 = 3 ^ 2 = 9
Multiply by 2
2 * 9 = 18
_______________________________________
2 ( x ^ 2 - 6 x + 9 ) + 11 - 18 =
2 ( x ^ 2 - 6 x + 9 ) - 7 =
______________________________________
Exspress x ^ 2 - 6 x + 9 as a square:
x ^ 2 - 6 x + 9 = ( x - 3 ) ^ 2
______________________________________
2 ( x - 3 ) ^ 2 - 7
2 ( x ^ 2 - 6 x ) + 11 =
______________________________________
Take one half of the coefficient of x and square it.
In this case : [ ( 1 / 2 ) * 6 ] ^ 2 = 3 ^ 2 = 9
Multiply by 2
2 * 9 = 18
_______________________________________
2 ( x ^ 2 - 6 x + 9 ) + 11 - 18 =
2 ( x ^ 2 - 6 x + 9 ) - 7 =
______________________________________
Exspress x ^ 2 - 6 x + 9 as a square:
x ^ 2 - 6 x + 9 = ( x - 3 ) ^ 2
______________________________________
2 ( x - 3 ) ^ 2 - 7